Perception and Practices of Colonoscopy Procedure: A Nationwide Survey of Indian Gastroenterologists - Jha, Jitendra Mohan; Babu, Sethu (Journal of Digestive Endoscopy, 2020)
Introduction There is a lack of data and consensus about the practices and policies regarding performing colonoscopy in India. We surveyed gastroenterologists to assess their practices and policies of performing colonoscopy.Methodology A questionnaire was presented to gastroenterologists all over India regarding their preference of bowel preparation and method of sedation, completeness of cecal and ileal intubation rates, preferences for inflation, use of carbon dioxide and nitrous oxide, and complications faced.Results Of the 350 surveys, 307 had completely responded (88%). Only 18% of the centers were conducting more than 100 colonoscopies a month and 46% denied following a colon cancer screening policy. Two bottles of liquid polyethylene glycol were the most preferred preparation. A total of 21% did not prefer any sedation at all. Nitrous oxide was used by only 5.6% of doctors. Ileal intubation rate was >96% in 34% of centers and cecal intubation rate >96% in 58% of centers. Air was used for inflation by 58%, while 39% used CO2. A total of 40% of the respondents believe CO2 inflation would improve cecal intubation rate, while 9.4% believed otherwise. While one third found CO2 inflation unnecessary and 14% not cost-effective, three fourths were still interested in setting up a CO2 facility. Reasons for not using nitrous oxide were practical/administrative difficulty (46.6%), side effects (20%), and cost (16%). Still more than half surveyed would consider using Entonox in future. Perforation was the most noted complication faced by respondents.Conclusions This survey of real-world clinical practices will help to formulate practice guideline regarding colonoscopy in India.
Keywords: colonoscopy; colon cancer; screening; survey